Does Disaster Knowledge Matter? Examining Community-Based Flood Mitigation in a Developing Country Context - Lalu Ahmad Murdhani; Mei Susanti (Yayasan Hisnul Muslim Lombok, 2025)
Floods remain one of the most recurrent and damaging hazards in developing countries, where structural limitations and governance challenges often constrain disaster risk reduction efforts. While disaster knowledge is frequently promoted as a key component of community-based disaster risk reduction, empirical evidence on how different forms of knowledge influence flood mitigation practices remains limited. This study examines the role of disaster knowledge in shaping community-based flood mitigation in a developing country context. Using a descriptive qualitative approach, data were collected through semi-structured interviews and non-participant observations in a flood-prone community in Indonesia. The analysis was guided by the Revised Bloom’s Taxonomy, which conceptualizes disaster knowledge into factual, conceptual, procedural, and metacognitive dimensions. Thematic analysis was employed to identify patterns linking knowledge dimensions to mitigation practices. The findings reveal that disaster knowledge matters, but its influence varies across cognitive dimensions. Factual knowledge primarily increases awareness but has limited impact on sustained mitigation actions. Conceptual knowledge enhances collective understanding of flood risk and encourages community engagement, while procedural knowledge directly enables practical mitigation measures. Metacognitive knowledge, although less prevalent, supports adaptive learning and reflective decision-making. However, the translation of knowledge into mitigation practices is constrained by economic and governance-related factors. This study contributes to disaster risk reduction literature by applying a multidimensional cognitive framework to flood mitigation and highlights the need for capacity-building strategies that move beyond awareness toward actionable and reflective knowledge.